Factors associated with an increased risk of SARS-CoV-2 infection in healthcare workers in aerosol-generating disciplines - Römmele, Christoph; Kahn, Maria; Zellmer, Stephan; Muzalyova, Anna; Hammel, Gertrud; Bartenschlager, Christina; Beyer, Albert; Rosendahl, Jonas; Schlittenbauer, Tilo; Zenk, Johannes; Al-Nawas, Bilal; Frankenberger, Roland; Hoffmann, Juergen; Arens, Christoph; Lammert, Frank; Traidl-Hoffmann, Claudia; Messmann, Helmut; Ebigbo, Alanna (Zeitschrift für Gastroenterologie, 2022)
Background Healthcare workers (HCWs) are at a high risk of SARS-CoV-2 infection due to exposure to potentially infectious material, especially during aerosol-generating procedures (AGP). We aimed to investigate risk factors for SARS-CoV-2 infection among HCWs in medical disciplines with AGP.Methods A nationwide questionnaire-based study in private practices and hospital settings was conducted between 12/16/2020 and 01/24/2021. Data on SARS-CoV-2 infections among HCWs and potential risk factors of infection were investigated.Results 2070 healthcare facilities with 25113 employees were included in the study. The overall infection rate among HCWs was 4.7%. Multivariate analysis showed that regions with higher incidence rates had a significantly increased risk of infection. Furthermore, hospital setting and HCWs in gastrointestinal endoscopy (GIE) had more than double the risk of infection (OR 2.63; 95% CI 2.50–2.82, p<0.01 and OR 2.35; 95% CI 2.25–2.50, p<0.01). For medical facilities who treated confirmed SARS-CoV-2 cases, there was a tendency towards higher risk of infection (OR 1.39; 95% CI 1.11–1.63, p=0.068).Conclusion Both factors within and outside medical facilities appear to be associated with an increased risk of infection among HCWs. Therefore, GIE and healthcare delivery setting were related to increased infection rates. Regions with higher SARS-CoV-2 incidence rates were also significantly associated with increased risk of infection.
Keywords: Aerosol-generating procedures; SARS-CoV-2; Prevalence; endoscopy; risk factors; COVID-19